Chinese business networks : state, economy and culture (Singapore : Prentice Hall ; Nordic Institute of Asian Studies, 2000)
Trust and its limitations: a changing discourse on money during the people's Republic of China's reform period. Trasaction cost, cultural values and Chinese business networks...
Keywords: Economics; China; Business networks; Businesspeople; Business networks -- China; Businesspeople -- China -- Social networks; Business ethics -- China; Business enterprises -- Southeast Asia; Business networks -- Southeast Asia; Businesspeople -- Southeast Asia -- Social networks; Business ethics -- Southeast Asia; Chinese language